(untitled) (Research, Society and Development, 2022)
The reconstruction of the posterior region of atrophic maxillae, aiming at rehabilitation with dental implants, is considered a challenge. Maxillary sinus floor elevation surgery has become essential for bone height gain in this region. The maxillary sinus lift technique was initially described in 1977 and has undergone modifications over the years. Currently, several variations of the original technique have been used to provide access and allow elevation of the sinus membrane. However, the technique by accessing the lateral window is performed on a large scale to allow a safe and efficient path for bone grafting in the region. In planning, in order to avoid complications, the anatomical and systemic knowledge of the patient is crucial. The approach via the lateral window consists of making a bone window in the lateral wall of the maxillary sinus, allowing the lifting of the membrane and the apposition of a biomaterial under it. To obtain success in the technique, it is essential that the patient presents ideal systemic conditions, the professional is aware of their indications and contraindications. In addition, the choice of biomaterial and the surgical time for implant placement can be determining factors for the success of the surgery.